2009
DOI: 10.1093/toxsci/kfp150
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Suppressors of Cytokine Signaling by the Trichothecene Deoxynivalenol in the Mouse

Abstract: Deoxynivalenol (DON), a trichothecene mycotoxin found in grains and cereal-based foods worldwide, impairs weight gain in experimental animals but the underlying mechanisms remain undetermined. Oral exposure to DON induces rapid and transient upregulation of proinflammatory cytokine expression in the mouse. The latter are known to induce several suppressors of cytokine signaling (SOCS), some of which impair growth hormone (GH) signaling. We hypothesized that oral exposure to DON will induce SOCS expression in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 64 publications
6
43
0
Order By: Relevance
“…Thus, in terms of wound healing, ribosomal insult-induced SOCS3 could retard the regeneration or restitution process after ribosomal stress-induced mucosal injuries. Moreover, the growth-inhibitory action via SOCS is consistent with the findings of recent studies on the suppression of growth-related signals (69,70). According to these reports, DON (a chemical ribosomal stress agent) induced SOCS proteins after the onset of proinflammatory cytokine decline, and this induction was involved in impaired growth hormone signaling in liver.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, in terms of wound healing, ribosomal insult-induced SOCS3 could retard the regeneration or restitution process after ribosomal stress-induced mucosal injuries. Moreover, the growth-inhibitory action via SOCS is consistent with the findings of recent studies on the suppression of growth-related signals (69,70). According to these reports, DON (a chemical ribosomal stress agent) induced SOCS proteins after the onset of proinflammatory cytokine decline, and this induction was involved in impaired growth hormone signaling in liver.…”
Section: Discussionsupporting
confidence: 89%
“…Studies in animal models and immortalized cell lines have also shown that DON exposure modulates immune function by specifically influencing proinflammatory responses and white blood cell distribution and proliferation in several organs [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The primary mode of action of DON is thought to be its ability to bind to eukaryotic ribosomes and thereby inhibit protein synthesis [8,11]. Secondary mechanisms such as disruption of cell signaling, differentiation, growth and macromolecular synthesis have also been associated with DON exposure [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…Anorexia induced by DON is of particular concern from the perspective of human and animal health (Forsell et al, 1986;Iverson et al, 1995;JECFA, 2011). However, the mechanistic basis for this adverse effect remains not fully understood but likely results from upregulation of proinflammatory cytokines and neuroendocrine hormones that influence food intake and appetite (Amuzie et al, 2009;Flannery et al, 2011;Girardet et al, 2011a;Wu et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…DON can stimulate TNF-α and IL-1β mRNA expression and protein secretion in human monocyte cell lines, human peripheral blood monocytes and mouse macrophage cell lines (Wong et al, 1998;SugitaKonishi and Pestka, 2001;Chung et al, 2003;He et al, 2013). Exposure of animals to DON also evokes robust production of TNF-α and IL-1β in plasma (Zhou et al, 1999;Islam and Pestka, 2006) and many organs including the spleen, liver, kidney, lung and brain (Amuzie et al, , 2009Girardet et al, 2011b). Increased cytokine gene transcription and enhanced mRNA stability contribute to DON-induced upregulation of proinflammatory cytokine mRNAs and ultimately, proteins (Pestka, 2010b).…”
Section: Introductionmentioning
confidence: 99%